Micro-electro-fluidic grids for nematodes: A lens-less, image-sensor-less approach for on-chip tracking of nematode locomotion - Liu, Peng (2013)
This paper reports on the development of a lens-less and image-sensor-less micro-electro-fluidic (MEF) approach for real-time monitoring of the locomotion of microscopic nematodes. The technology showed promise for overcoming the constraint of the limited field of view of conventional optical microscopy, with a relatively low cost, good spatial resolution, and high portability. The core of the device was microelectrode grids formed by orthogonally arranging two identical arrays of microelectrode lines. The two microelectrode arrays were spaced by a microfluidic chamber containing a liquid medium of interest. As a nematode (e.g., Caenorhabditis elegans) moved inside the chamber, the invasion of its body parts into some intersection regions between the microelectrodes caused changes in electrical resistance of these intersection regions. The worm's presence at or absence from a detection unit was determined by a comparison between the measured resistance variation of this unit and a pre-defined threshold resistance variation. An electronic readout circuit was designed to address all detection units and read out their individual electrical resistance. By this means, it was possible to obtain the electrical resistance profile of the whole MEF grids, and thus, the physical pattern of the swimming nematode. We studied the influence of a worm's body on the resistance of an addressed unit. We also investigated how the full-frame scanning and readout rate of the electronic circuit and the dimensions of a detection unit posed an impact on the spatial resolution of the reconstructed images of the nematode. Other important issues, such as the manufacturing induced initial non-uniformity of the grids and the electrotaxic behaviour of nematodes, were also studied. A drug resistance screening experiment was conducted by using the grids with a good resolution of 30 × 30 μm(2). The phenotypic differences in the locomotion behaviours (e.g., moving speed and oscillation frequency extracted from the reconstructed images with the help of software) between the wild-type (N2) and mutant (lev-8) C. elegans worms in response to different doses of the anthelmintic drug, levamisole. The locomotive parameters obtained by the MEF grids agreed well with those obtained by optical microscopy. Therefore, this technology will benefit the whole-animal assays by providing a structurally simple, potentially cost-effective device capable of tracking the movement and phenotypes of important nematodes in various microenvironments.